LEARNING TO SPEAK WITH EFFORTLESS ENGLISH SYSTEM - Achmad Basari (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2011)
This article discusses an introduction to the new teaching system in the speaking classroom. This system is known as the Effortless English System. It is a system which relies much on listening activity. In recent years, most English students in schools have been stuck on a grammar-translation method. In practice, the students focus more on grammar rules teaching and translation. The results of this method show no improvement to their speaking skills. They tend to always think and translate before they speak. It obviously prevents them from being fluent and confident when speaking to other English students or to native speakers. On the other hand, Effortless English system teaches the students with fun and interesting stories. The system does not teach grammar rules consciously and analytically, instead it uses mini-story lessons to learn grammar intuitively. The major focus on this system is learning to speak by listening not by speaking. Speaking is optional after one listens to a lot of comprehensible inputs to his/her brain. Forced speaking is not recommended because it may damage final results. Listening to things that are always right will build the language right while saying things that are always wrong will build it wrong. The key to excellent speaking is listen to one thing many times not listen to many things one time. If students follow these rules, they will end up speaking English like a native. Keywords: Effortless English System, Comprehensible Inputs, Forced Speaking, Listening Activity